Influence Of Financial Performance On Carbon Performance In Companies Disclosing Sustainability Reports In Indonesia - Wasti Margaretha, Widya; Ferinluary, Fadila; Anjarsari, Putri Salsa; Febrila, Ariqo; Mukhzarudfa; Kusumastuti, Ratih; Putra, Wirmie Eka (Islamic Economics Department, Faculty of Islamic Economics and Business, UIN SULTHAN THAHA SAIFUDDIN JAMBI, 2024)
Business is essential for a country’s economic development, especially for its citizens. The purpose of this study is to investigate how financial performance affects carbon performance in companies listed on the Indonesia Stock Exchange (IDX) that report sustainability in 2020–2023. Leverage, Size, ROA, Capsend, and TobinQ are used to measure financial performance as the dependent variable. Greenhouse gas emission disclosure is used to measure carbon performance (CP), the independent variable. Companies reporting carbon emissions on the Indonesia Stock Exchange are 934 companies that publish sustainability reports. A total of 44 Indonesian businesses that are willing to be involved in releasing sustainability reports between 2020 and 2023 are the study samples. T-test and F-test are two multiple linear regression tests used by the author. In addition, this study offers empirical support for the ways in which businesses can communicate their underlying carbon performance through the use of some form of carbon information. According to the study findings, leverage, size, capsend, and tobinq have no effect on CP; only ROA has an effect. CP is simultaneously affected by leverage, size, ROA, capsend, and tobinQ because businesses with more resources usually have better sustainability reports and are more aware of climate change impacts. This is in line with signaling theory, which states that a company's strong financial results are an indication of its operational success.